2002
DOI: 10.1128/aem.68.4.1882-1892.2002
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Dynamics, and Activity of Bacterial Communities during Production of an Artisanal Sicilian Cheese as Evaluated by 16S rRNA Analysis

Abstract: The diversity and dynamics of the microbial communities during the manufacturing of Ragusano cheese, an artisanal cheese produced in Sicily (Italy), were investigated by a combination of classical and cultureindependent approaches. The latter included PCR, reverse transcriptase-PCR (RT-PCR), and denaturing gradient gel electrophoresis (DGGE) of 16S rRNA genes (rDNA). Bacterial and Lactobacillus group-specific primers were used to amplify the V6 to V8 and V1 to V3 regions of the 16S rRNA gene, respectively. DGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
235
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(258 citation statements)
references
References 41 publications
17
235
0
6
Order By: Relevance
“…In contrast to our study that focused on a single farm, the aforementioned authors analysed cheese samples of different origins. The average count of lactic acid bacteria was of the order of magnitude of 10 8 CFU/g in both monitored types of cheese (Table 4) and was in agreement with the data generally reported for raw cheese (Randazzo et al 2002). The presence of B. cereus was not detected in any of the samples.…”
Section: Resultssupporting
confidence: 89%
“…In contrast to our study that focused on a single farm, the aforementioned authors analysed cheese samples of different origins. The average count of lactic acid bacteria was of the order of magnitude of 10 8 CFU/g in both monitored types of cheese (Table 4) and was in agreement with the data generally reported for raw cheese (Randazzo et al 2002). The presence of B. cereus was not detected in any of the samples.…”
Section: Resultssupporting
confidence: 89%
“…Taking into account this drawback of culture-independent PCR approach, identical ARDRA profiles could be explained although initial diverse profiles were expected due to the use of raw milk in the cheese production. It has been reported by other authors [3,4,11,14,15] that population structure of LAB community present in the traditional raw milk cheeses is diverse and complex. The dominance of only one species was also confirmed by PCR-DGGE.…”
Section: Resultsmentioning
confidence: 98%
“…Molecular analysis of the Stilton cheese demonstrated that the use of different targets of the same DNA template revealed remarkably different results [6]. Moreover, partial 16S rDNA sequences do not always allow discrimination between closely related species and one band may represent two species with identical partial sequence [12,[14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, milk can accommodate numerous microbial species (Delbes et al, 2007). However, strong selective pressures like heat treatment (Van Hoorde et al, 2008), dairy processing conditions (Randazzo et al, 2002), intrinsic properties of lactic acid fermentation and antagonistic interactions (Lindgren and Dobrogosz 1990), enrich the microbiota toward a few lactic acid bacteria species.…”
Section: Discussionmentioning
confidence: 99%